2011
DOI: 10.1097/mcd.0b013e328348d99d
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in fetuses with ultrasonographically detected neural tube defects

Abstract: We analyzed the karyotype of fetuses with ultrasonographically detected neural tube defects (NTDs). In our study, we included a total of 194 fetuses with NTDs. We analyzed the type of NTD, the karyotype, maternal age, fetal gestational age at diagnosis, and fetal sex. Of the 194 fetuses with NTDs, 87 were anencephalic and 107 had other, nonanencephalic, NTDs. A total of 12 fetuses were shown to have chromosomal abnormalities. Three of 87 anencephalic fetuses (3.45%) had chromosomal abnormalities. The sex ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…2.3% in anencephaly, 7.1% in encephalocele, and 10.2% in meningomyelocele [22]. It is consistent across several studies that encephalocele have higher chromosomal abnormality rate than anencephaly, and spina bifida have higher chromosomal abnormality rate than craniorachischisis [41], [42], [43]. Among all the detected chromosomal abnormalities, trisomy was the most common chromosomal abnormality associated with NTDs [43].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2.3% in anencephaly, 7.1% in encephalocele, and 10.2% in meningomyelocele [22]. It is consistent across several studies that encephalocele have higher chromosomal abnormality rate than anencephaly, and spina bifida have higher chromosomal abnormality rate than craniorachischisis [41], [42], [43]. Among all the detected chromosomal abnormalities, trisomy was the most common chromosomal abnormality associated with NTDs [43].…”
Section: Discussionsupporting
confidence: 81%
“…1) None of the cases harbored CNVs larger than 3 Mb, the majority of CNVs were between 100–500 kb in size and no trisomy was detected in this not previously screened NTD cohort. Previous studies identified large chromosomal abnormalities including trisomy in a significant percentage of NTD cases among patients from Western countries [21], [22], [23], [41], [42]; this phenomenon may indicate underlying genetic differences between our cohort collected in Shanxi region and cases collected for previous studies. 2) The NTD cases collected for this study consisted of many cases with additional malformations outside the nervous system.…”
Section: Discussionmentioning
confidence: 63%
“…Two of these had trisomy 18, and both had OMP (Ekin et al, ). A wide array of other sources suggest higher NTD incidence in aneuploidy (Hume et al, ; Kanit et al, ; Kennedy, Chitayat, Winsor, Silver, & Toi, ; Nielsen, Maroun, Broholm, Laursen, & Graem, ; Sepulveda et al, ; Stoll, Alembik, Dott, & Roth, ).…”
Section: Discussionmentioning
confidence: 99%
“…15 In less than 10% of cases, spina bifida is due to genetic syndromes or chromosomal anomalies, including the common trisomies 13 and 18, triploidy and microdeletions or duplications. [16][17][18] Most of these fetuses would present with anomalies in different organ systems 19 What's already known about this topic?…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%